Moderating Role of Health Services and Personnel on the Relationship between Education, Income, and Crude Birth Rate in Bogor Regency, Indonesia - Budi Susetyo; Novel Anak Lyndon; Yuggo Afrianto; Riny Kusumawati; Widyasari Widyasari; Fety Fatimah; Desmy Riani (Journal of Governance and Public Policy, 2024)
This study examined the factors that influence the crude birth rate (CBR) in Bogor Regency, Indonesia. The study objectives were to (1) determine the relationship between education and CBR, (2) determine the relationship between income and CBR, and (3) determine the moderating effect of healthcare services and personnel on the relationship between education and CBR. A cross-sectional survey was conducted with a sample of 259 respondents. The data were collected using a structured questionnaire. The data were analyzed using descriptive statistics, regression analysis, and moderating effect analysis. The results show that education and income have a significant impact on CBR. However, income has a non-linear relationship. Higher income can lower the CBR in the Bogor district. Health services can moderate the relationship between education and CBR. The findings of this study suggest that education and income are important factors that influence CBR in Bogor Regency.